2018
DOI: 10.4108/eai.27-1-2021.168502
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Kinematic analysis of 3-RRR Planar Parallel Manipulator

Abstract: Parallel mechanisms are found as positioning platforms in several robot manipulator applications tool manufacturing applications. Today, various types of these mechanisms are classified based on the structure, type of joints, and degree of freedom. An important and basic planar mechanism providing three degrees of freedom at the end-effector (movable platform) is a 3-RRR linkage. The forward kinematics in parallel mechanisms is a multi-solution problem and involves cumbersome calculations compared to inverse k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study of Chablat et al 10 showed a recursive modeling for the kinematics of a 3-PRP planar parallel manipulator with vertical legs, focusing on the computing of the kinematic parameters and singularities. Shahed et al 11 computed the dimensions and established the practical and dexterous workspace available at the end-effector of a planar parallel manipulator 3- R RR. Wang 12 optimized the overall transmission performance of a 3- R RR planar parallel manipulator with optimal shapes and sizes of platform.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Chablat et al 10 showed a recursive modeling for the kinematics of a 3-PRP planar parallel manipulator with vertical legs, focusing on the computing of the kinematic parameters and singularities. Shahed et al 11 computed the dimensions and established the practical and dexterous workspace available at the end-effector of a planar parallel manipulator 3- R RR. Wang 12 optimized the overall transmission performance of a 3- R RR planar parallel manipulator with optimal shapes and sizes of platform.…”
Section: Introductionmentioning
confidence: 99%